Increased and imbalanced dNTP pools symmetrically promote both leading and lagging strand replication infidelity. - Robert J Buckland; Danielle L Watt; Balasubramanyam Chittoor; Anna Karin Nilsson; Thomas A Kunkel; Andrei Chabes (PLoS Genetics)
The fidelity of DNA replication requires an appropriate balance of dNTPs, yet the nascent leading and lagging strands of the nuclear genome are primarily synthesized by replicases that differ in subunit composition, protein partnerships and biochemical properties, including fidelity. These facts pose the question of whether imbalanced dNTP pools differentially influence leading and lagging strand replication fidelity. Here we test this possibility by examining strand-specific replication infidelity driven by a mutation in yeast ribonucleotide reductase, rnr1-Y285A, that leads to elevated dTTP and dCTP concentrations. The results for the CAN1 mutational reporter gene present in opposite orientations in the genome reveal that the rates, and surprisingly even the sequence contexts, of replication errors are remarkably similar for leading and lagging strand synthesis. Moreover, while many mismatches driven by the dNTP pool imbalance are efficiently corrected by mismatch repair, others are repaired less efficiently, especially those in sequence contexts suggesting reduced proofreading due to increased mismatch extension driven by the high dTTP and dCTP concentrations. Thus the two DNA strands of the nuclear genome are at similar risk of mutations resulting from this dNTP pool imbalance, and this risk is not completely suppressed even when both major replication error correction mechanisms are genetically intact.